Neuroprotective Role of the Ron Receptor Tyrosine Kinase Underlying Central Nervous System Inflammation in Health and Disease - Dey, Adwitia; Allen, Joselyn N.; Fraser, James W.; Snyder, Lindsay M.; Tian, Yuan; Zhang, Limin; Paulson, Robert F.; Patterson, Andrew; Cantorna, Margherita T.; Hankey-Giblin, Pamela A. (Frontiers in Immunology, 2018)
Neurodegeneration is a critical problem in aging populations and is characterized by severe central nervous system (CNS) inflammation. Macrophages closely regulate inflammation in the CNS and periphery by taking on different activation states. The source of inflammation in many neurodegenerative diseases has been primarily linked to a decrease in the CNS M2 macrophage population and a subsequent increase in M1 mediated neuroinflammation. The Ron receptor tyrosine kinase is expressed on tissue resident macrophages including microglia. Activation of Ron by its ligand, MSP, attenuates obesity mediated inflammation in the periphery. An in vivo deletion of the ligand binding domain of Ron (Ron-/-) promotes inflammation (M1) and limits a reparative (M2) macrophage activation. However, whether or not this response influences CNS inflammation has not been determined. In this study, we demonstrate that in homeostasis Ron-/- mice developed an inflammatory CNS niche with increased tissue expression of M1-associated markers when compared to age-matched WT mice. Baseline metabolic analysis of CNS tissue indicates exacerbated levels of metabolic stress in Ron-/- CNS. In a disease model of multiple sclerosis, experimental autoimmune encephalomyelitis (EAE), Ron-/- mice exhibit higher disease severity when compared to WT mice associated with increased CNS inflammation. In a model of diet induced obesity (DIO) Ron-/- mice exhibit exacerbated CNS inflammation with decreased expression of the M2 marker Arginase-1 (Arg-1) and a robust increase in M1 markers compared to WT mice following 27 weeks of DIO. Collectively, these results illustrate that activation of Ron in the CNS could be a potential therapeutic approach to treating various grades of CNS inflammation underlying neurodegeneration.